Perencanaan Sumber Daya Manusia dan Peningkatan Daya Saing Produk melalui Strategi Pengemasan pada Usaha Mikro Seblak Mamih di Kabupaten Bandung - Terra Saptina Maulani; Rr. Rachmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
The creative economy sector is one of the pillars of economic growth in Indonesia where creativity is the basis of economic development activities. West Java Province is one of the provinces in Indonesia with a high distribution of the creative economy sector. Not only is Bandung City famous for its culinary, but currently Bandung Regency is an area that is starting to develop its culinary tourism. in the minds of tourists. One of the snacks or snacks that are popular with the community and also is seblak, this